The Problem of Akad Murabahah in Sharia Banks: Between Profit-Oriented and Sharia Compliance - Muhamad Rowi Kurniawan; Abdurrahman; Sinta Thia Anggraeni; Uswatun Hasanah; Marwiyah (Walidem Institute and Publishing (WIP), 2024)
This study aims to evaluate financing practices with murabahah contracts carried out by Islamic Banks in Indonesia. While this practice can generate significant profits, there are risks of adherence to sharia principles. The main issue involves the use of the wakalah contract and the existence of murabahah objects. Research shows that wakalah contracts are still made at the same time as murabahah contracts, and the existence of murabahah objects is not always ascertained by Islamic banks. In overcoming this dilemma, Islamic banks need to maintain a balance between seeking maximum profit and complying with Islamic financial principles. Strategies such as ensuring compliance with Sharia principles, product diversification, employee and customer education, building partnerships, developing technology, and maintaining transparency and accountability can be adopted. By implementing this strategy, Islamic banks are expected to achieve adequate profitability while still adhering to Sharia principles, strengthening their position in increasingly competitive financial markets.